Case report: Challenges in immune reconstitution following hematopoietic stem cell transplantation for CTLA-4 insufficiency-like primary immune regulatory disorders - Margarit-Soler, Adriana; Deyà-Martínez, Àngela; Canizales, Juan Torres; Vlagea, Alexandru; García-García, Ana; Marsal, Júlia; Del Castillo, Maria Trabazo; Planas, Sílvia; Simó, Sílvia; Esteve-Sole, Ana; Grande, María Suárez-Lledó; Badell, Isabel; et al. (Frontiers in Immunology, 2022)
CTLA-4 haploinsufficiency is a T cell hyperactivation disorder that can manifest with both immunodeficiency and immune dysregulation. Around one-third of patients may present mild symptoms and remain stable under supportive care. The remaining may develop severe multiorgan autoimmunity requiring life-long immunosuppressive treatment. HSCT is a potential curable option for patients with treatment-resistant immune dysregulation. Nevertheless, little experience is reported hampering the management of complications post-HSCT. We present case 1 (CTLA-4 haploinsufficiency) and case 2 (CTLA-4 deficiency-like phenotype) manifesting with severe autoimmunity including cytopenia and involvement of CNS, lung and gut, and variable impairment of humoral responses. Both patients underwent HSCT, for which main complications were persistent mixed chimerism, infections and immune-mediated complications (GVHD and nodular lung disease). Detailed management and outcomes of therapeutic interventions post-HSCT are discussed. Concretely, the use of post-HSCT abatacept and HLA-matched sibling donor lymphocyte infusions to increase T-cell donor chimerism, with the aim of correcting the immune phenotype of CTLA-4 haploinsufficiency.